Scaling the Balkans : Essays in National, Transnational and Conceptual History. - Todorova, Maria N. (Balkan studies library., 2018)
"Maria Todorova puts in conversation several fields that have been traditionally treated as discrete: Balkans, Eastern Europe, Ottoman, Habsburg and Russian empires. Applying different perspectives and different methodological approaches, it insists on the heuristic value of scales"--Provided by Publisher.